2019
DOI: 10.3389/fmicb.2019.01319
|View full text |Cite
|
Sign up to set email alerts
|

Soil Photosynthetic Microbial Communities Mediate Aggregate Stability: Influence of Cropping Systems and Herbicide Use in an Agricultural Soil

Abstract: Edaphic cyanobacteria and algae have been extensively studied in dryland soils because they play key roles in the formation of biological soil crusts and the stabilization of soil surfaces. Yet, in temperate agricultural crop soils, little is understood about the functional significance of indigenous photosynthetic microbial communities for various soil processes. This study investigated how indigenous soil algae and cyanobacteria affected topsoil aggregate stability in cereal cropping systems. Topsoil aggrega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 70 publications
(138 reference statements)
3
17
0
3
Order By: Relevance
“…Soil aggregate stability was significantly higher in algalized soils than that of DC or LC. One possible reason could be due to the biochemical composition of EPS derived from microalgae that favour cohesion and cementing of microaggregates as reported recently by Crouzet et al (2019). Of the two microalgal strains, MAS1 effected lower aggregate stability and the change in EPS production was less throughout the incubation period (Table 2, Figure 2).…”
Section: Resultsmentioning
confidence: 62%
“…Soil aggregate stability was significantly higher in algalized soils than that of DC or LC. One possible reason could be due to the biochemical composition of EPS derived from microalgae that favour cohesion and cementing of microaggregates as reported recently by Crouzet et al (2019). Of the two microalgal strains, MAS1 effected lower aggregate stability and the change in EPS production was less throughout the incubation period (Table 2, Figure 2).…”
Section: Resultsmentioning
confidence: 62%
“…Energy metabolism by means of the photosynthetic pathway was the highest in transition farming followed by organic farming and was significantly decreased in conventional farming, suggesting that higher energy was required to transform the agrochemical-polluted land into healthier farmland. This also indicated that the application of agrochemicals, especially herbicides, in the conventional practice reduced the photosynthetic potentials of the overall phyllosphere microbial communities (Broser et al, 2011;Crouzet et al, 2019). Furthermore, fertilization in the conventional farm could also alter the composition of leaf exudates (Barunawati et al, 2013), which might not favor its associated phyllosphere colonizers.…”
Section: Discussionmentioning
confidence: 99%
“…Actinomycetes resemble both the bacteria and fungi, they have antibiotic properties and as well secrete metabolites that enhance plant growth and drive away pests (Singh et al, 2018). Algae are photosynthetic organisms that live in the soil, enhance the weathering of soil parent material, hold together the soil particles, and when they die, they increase the soil organic matter content (Crouzet et al, 2019). Protozoa are organisms that have antimicrobial properties and help regulate the bacterial population in the soil by feeding on them (Gaines et al, 2019).…”
Section: Linking Plant Microbiome Composition With Functionmentioning
confidence: 99%